Investigation of the effect on prostate cancer purine base analog of the newly developed compound - Gokhan Temeltas; Funda Kosova; Ozlem Temiz Arpaci; Ibrahim Tuglu (Medicine Science, 2020)
Prostate cancer is an important cause of death in men. This malignant disease is known for excessive proliferation, decreased apoptosis, and uncontrolled proliferation of cells. In the light of this knowledge, our aim was to examine potential compounds for their effects on NF-κB and angiogenesis proteins (VGEF, MMP, ES, TSP-1) in a prostate cancer line. In this study, we planned that the purine base analogue with anti-cancer potential has synthesized new compounds, and those with anti-cancer potential has selected by screening with MTT testing. We analysed VEGF, MMP, Endostatin (ES), Thrombospondin-1 (TSP-1) and NF-κB protein levels in a prostate cancer line by the Elisa method. MMA-MEP caused a significant decrease especially for VEGF-A, NF-kB, Endostatin, Thrombospondin -1 and MMP levels compared to other compounds. This suggests that this heterocyclic compound is more effective compared to others. This compound could be more effective for patients with prostate cancer, depending on time and amount. In line with these results, we want to continue our work by applying this heterocyclic compound in different amounts at different time periods. [Med-Science 2020; 9(4.000): 823-8]